Liver Transplantation After Ex Vivo Normothermic Machine Preservation: A Phase 1 (First‐in‐Man) Clinical Trial. Issue 6 (7th March 2016) - Ravikumar, R.; Jassem, W.; Mergental, H.; Heaton, N.; Mirza, D.; Perera, M. T. P. R.; Quaglia, A.; Holroyd, D.; Vogel, T.; Coussios, C. C.; Friend, P. J.
Abstract : The number of donor organs suitable for liver transplantation is restricted by cold preservation and ischemia–reperfusion injury. We present the first patients transplanted using a normothermic machine perfusion (NMP) device that transports and stores an organ in a fully functioning state at 37°C. In this Phase 1 trial, organs were retrieved using standard techniques, attached to the perfusion device at the donor hospital, and transported to the implanting center in a functioning state. NMP livers were matched 1:2 to cold‐stored livers. Twenty patients underwent liver transplantation after NMP. Median NMP time was 9.3 (3.5–18.5) h versus median cold ischaemia time of 8.9 (4.2–11.4) h. Thirty‐day graft survival was similar (100% NMP vs. 97.5% control, p = 1.00). Median peak aspartate aminotransferase in the first 7 days was significantly lower in the NMP group (417 IU [84–4681]) versus (902 IU [218–8786], p = 0.03). This first report of liver transplantation using NMP‐preserved livers demonstrates the safety and feasibility of using this technology from retrieval to transplantation, including transportation. NMP may be valuable in increasing the number of donor livers and improving the function of transplantable organs. Abstract : This article describes 20 patients who underwent successful transplantation of livers preserved using normothermic perfusion, with results similar to matched controls, confirming the safety and feasibility of this novel preservation method. See the editorial onpage 1647 from Guarrera.